A depth-dependent formula for shallow water propagation - Sertlek, Huseyin Ozkan; Ainslie, Michael A. (Acoustical Soc Amer Amer Inst Physics, 2014)
In shallow water propagation, the sound field depends on the proximity of the receiver to the sea surface, the seabed, the source depth, and the complementary source depth. While normal mode theory can predict this depth dependence, it can be computationally intensive. In this work, an analytical solution is derived in terms of the Faddeeva function by converting a normal mode sum into an integral based on a hypothetical continuum of modes. For a Pekeris waveguide, this approach provides accurate depth dependent propagation results (especially for the surface decoupling) without requiring complex calculation methods for eigenvalues and corresponding eigenfunctions. (C) 2014 Acoustical Society of America.
Keywords: Mode Attenuation; Reflection Loss; Sound; Cycle